Leveraging mice with diverse microbial exposures for advances in osteoimmunology - Little-Letsinger, Sarah E.; Hamilton, Sara E. (Frontiers in Endocrinology, 2023)
The skeletal and immune systems are intricately intertwined within the bone marrow microenvironment, a field of study termed osteoimmunology. Osteoimmune interactions are key players in bone homeostasis and remodeling. Despite the critical role of the immune system in bone health, virtually all animal research in osteoimmunology, and more broadly bone biology, relies on organisms with naïve immune systems. Drawing on insights from osteoimmunology, evolutionary anthropology, and immunology, this perspective proposes the use of a novel translational model: the dirty mouse. Dirty mice, characterized by diverse exposures to commensal and pathogenic microbes, have mature immune systems comparable to adult humans, while the naïve immune system of specific-pathogen free mice is akin to a neonate. Investigation into the dirty mouse model will likely yield important insights in our understanding of bone diseases and disorders. A high benefit of this model is expected for diseases known to have a connection between overactivation of the immune system and negative bone outcomes, including aging and osteoporosis, rheumatoid arthritis, HIV/AIDS, obesity and diabetes, bone marrow metastases, and bone cancers.